Exchange Rate Exposure on Indonesian Firms Listed in Indonesian Stock Exchange (Study on Indonesian Super USD Phenomenon) - Mikhail Antony Septryan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to investigate whether the exchange rate exposure of Indonesian firms are significant within the issue of Super USD phenomenon occurring in 2015. The exposure measured using symmetric and asymmetric models to analyze daily data of Indonesian firms from May 2015 to September 2016 in sectoral and individual levels. The firms selected from mining, agriculture, consumer industry, and basic industry sectors. The result of this research shows that the issue does not significantly affect Indonesian firms, in general. It is only small percentage of Indonesian firms affected and only the mining sector constantly comes with significant result of the exposure specifically with symmetric exposure. The results also shows that Indonesian firms have more possibility to be exposed asymmetrically but it is not significant. The exposure results are positive in average as the significant increases did not occur and the firms are stimulated with the good condition of Indonesian economic.Keyword: exchange rate exposure, sectoral and individual levels, Super USD.